Comparison of Continuous Core Profiles and Monitoring Wells for Assessing Groundwater Contamination by Agricultural Nitrate. Issue 1 (26th February 2015) - Bourke, Sarah A.; Turchenek, Jonathan; Schmeling, Erin E.; Mahmood, F. Nessa; Olson, Barry M.; Hendry, M. Jim
Abstract: Studies that assess groundwater contamination by agricultural nitrate (NO3 − ) commonly measure groundwater chemistry in samples collected from monitoring wells. This approach can be limited by coarse vertical resolution and aquifer heterogeneity. In this paper, we compare continuous core profiles against samples from monitoring wells for assessing agricultural nitrate contamination. Stable isotopes (δ 2 H and δ 18 O), chloride (Cl − ), and NO3 − were measured in four nested wells and continuous core collected to depths of up to 20 m on three different sampling dates at a site in Alberta, Canada. Continuous core profiles of stable isotopes are used to define solute transport zones (advection‐dispersion dominated vs. diffusion dominated), which then informs the interpretation of the Cl − and NO3 − profiles. Data from monitoring wells were particularly useful for capturing the temporal dynamics near the water table, but could not be used to define the dominant transport zones. Given the temporal variation in mass input of agricultural NO3 −, the increased spatial resolution of continuous core profiles provides an advantage over samples from monitoring wells to assess groundwater contamination by agricultural NO3 − . The relatively fine spatial resolution of continuous core profiles is particularly useful for assessing rates of NO3 − attenuation through denitrification. This benefit is offset by the need to resample the entire profile at each sampling time, in contrast to groundwater wells, which can be sampled repeatedly with time. Vertical profiling of continuous core is recommended in addition to monitoring wells to assess near‐surface groundwater contamination, particularly at sites where vertical heterogeneity in hydraulic conductivity on the scale of metres or less is likely.